INVENTORY OF MACROFUNGI DIVERSITY ON THE CANOPY TRACK AND CIPADARANTEN 1 TRACK IN THE PPKA BODOGOL AREA, SUKABUMI, WEST JAVA - Amlimny, Aniza Fitria; Ningrum, Novalia Widya; Jannah Jamil, Aisyah Wardatul; Maryana, Kamilia Fadhilah; Naufananda, Demas Athallah; Utami, Annisa Wulan Agus; Miarsyah, Mieke (Universitas Pattimura, 2023)
The inventory of macrofungi diversity on two routes, namely the Kanopi route and the Cipadaranten 1 route at the Bodogol Nature Conservation and Education Center (PPKA), aims to determine the diversity of macrofungi species that live in the area. The research method used is direct observation in the Canopy and Cipadaranten 1 route areas. With the condition of the trees on both routes which are still quite dense and the soil area is still damp due to the cover of the trees, there is great potential for the growth of various types of macrofungi. The results obtained during research on both routes and identification produced 24 species of macrofungi Microporus sp. 1, Microporus sp. 2, Microporus sp. 3, Trametes sp.1, Lenzites sp, Ganoderma sp., Ganoderma boninense, Trametes sp.2, Microporus xanthopus, Hexagonia sp, Trametes parvispora, Microporus sp. 4, Hygrocybe aurantiosplendens, Hygrocybe sp., Marasmius sp. 1, Collybia aurea, Crepidotus sp., Volvariella sp., Marasmius sp. 2, Lycoperdon sp., Marasmiellus sp. , Coprinus sp. , Stereum sp., Auricularia sp. The results obtained prove that the diversity of macrofungi types on the Kanopi and Cipadaranten 1 routes in PPKA Bodogol, West Java is very diverse and varied.